THE DETERMINANT ANALYSIS OF PROFITABILITY IN THE SHARIA BANKING INDUSTRY IN 2011-2018 USING AUTO REGRESSIVE DISTRIBUTED LAG (ARDL) APPROACH - Gita Martha Permatasari; Dian Filianti (Universitas Airlangga, 2020)
This study aims to determine the influence of the Macro Economy, namely GDP and Inflation and Bank Characteristics, namely CAR, FDR, NPF, BOPO and Size on the Profitability of the Sharia Banking Industry in Indonesia in the 2011 - 2018 Period. The data used are secondary data, namely quarterly data obtained from the official website of Bank Indonesia (www.bi.go.id), Badan Pusat Statistik (www.bps.go.id), and Statistik Perbankan Syariah reports published by OJK (www.ojk.go.id). The sampling method used was purposive sampling method. The analysis technique uses the ARDL (Autoregressive Distributed Lag) model with statistical tools EViews 9. The results of the study show that in the short term of the GDP, Inflation, BOPO, Size variables, they have a significant effect on the profitability of the Sharia Banking Industry and the CAR, FDR, NPF variables have no significant effect on profitability of Islamic Banking Industry. Meanwhile in the long run of the GDP, BOPO, Size variables, they have a significant effect on the profitability of the Sharia Banking Industry and the Inflation, CAR, FDR, NPF variable does not significantly influence the profitability of the Sharia Banking Industry.Keywords: Profitability, Sharia Bank, ARDLREFFERENCE Alharbi, Ahmad Thabet. (2017). Determinant of Islamic banks’ profitability: International evidence. International Journal of Islamic and Middle Eastern Finance and Management, 10(3), 331-350. DOI: https://doi.org/10.1108/IMEFM-12-2015-0161Abdurrahman dan Ahmad. (2018). Metode penelitian muamalah. Jakarta: Salemba Diniyah. Ali, Khizer. et. al. (2011). Bank specific and macro economic indicators of profitability empirical evidence from commercial banks Pakistan. International Journal of Business and Sosial Science, 2(6), 235-242.Almunawwaroh, Medina dan Marliana, Rina. (2018). Pengaruh CAR, NPF dan terhadap profitabilitas bank syariah di Indonesia. Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2(1), 1-18.Boediono. (2004). Ekonomi moneter. Yogyakarta: BPFE.Dendawijaya, Lukman. (2009). Manajemen perbankan. Jakarta: Penerbit Ghalia Indonesia.Djamil, Faturrahman. (2012). Penyelesaian pembiayaan bermasalah di bank syariah. Sinar Grafika: Jakarta.Harahap, Sofyan Syafri. (2009). Teori kritis laporan keuangan. Jakarta: Bumi Aksara. Jumingan.Haron, Sudin. (2004). Determinant of Islamic Bank Profitability. Global Journal of Finance and Economics, 1(1), 1-22.Hasibuan, Drs. H. Malayu S.P. (2007). Dasar-dasar Perbankan. Jakarta: PT Bumi Askara.Kasmir. (2012). Analisis laporan keuangan. Jakarta: Rajawali Pers.Madura, Jeff. (2007). Introduction to business, edisi keempat. Jakarta: Salemba Empat.Masood, Omar and Muhammad Ashraf. (2012). Bank-spesific and macroeconomics profitability determinants of Islamic banks: The case of different countries. Qualitative Research in Financial Markets, 4(2/3), 255-268. DOI: https://doi.org/10.1108/17554171211252565Nusantara, Ahmad Buyung. (2009). Analisis pengaruh NPL, CAR, LDR dan BOPO terhadap profitabilitas bank. Tesis tidak diterbitkan. Semarang: Universitas Diponegoro.Otoritas Jasa Keuangan. (2018). Statistik perbankan syariah. Diakses melalui www.ojk.go.id.Peraturan Bank Indonesia Nomor: 2/ 8 /PBI/2000.Rani, Lina Nugraha. (2013). Analisis faktor-faktor yang mempengaruhi non performing financing pada perbankan syariah di Indonesia periode 2003-2013. Tesis tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Ramlall, I. (2009). Bank-Specific, Industry Specific and Macroeconomic Determinants of Profitability in Taiwanese Banking System: Under Panel Data Estimation. International Research Journal of Finance and Economics, (34), 160- 167.Republik Indonesia. Undang-Undang No. 21 Tahun 2008 Tentang Perbankan Syariah.Rivai dan Andira. (2009). Bank and financial institution management. Jakarta. PT Raja Grafindo Persada. Riyadi, S. (2006). Banking assets and liability management, edisi ketiga. Jakarta: FE UI.Sahara, Ayu Yanita. (2013). Analisis pengaruh inflasi, suku bunga BI dan produk domestik bruto terhadap Return On Asset (ROA) bank syariah di Indonesia. Jurnal Ilmiah Mahasiswa UNESA.Samuelson, Paul A. Dan William D Nordhaus. (2004). Ilmu makroekonomi, edisi ketujuhbelas. Jakarta: PT Media Global Edukasi.Sodiq, Amirus. (2015). Pengaruh variabel makro ekonomi terhadap profitabilitas bank syariah di Indonesia periode 2009-2014. Jurnal Bisnis dan Manajemen Islam, 3(2), 343-363.Sugiyono. (2015). Metode penelitian kuantitatif, kualitatif, dan R&D. Bandung: Alfabeta.Sukirno. (2006). Ekonomi pembangunan: Proses, masalah, dan dasar kebijakan. Jakarta: Kencana.Suryani dan Hendryadi. (2016). Metode riset kuantitatif. Jakarta: PT. Fajar Interpretama Mandiri.Widyaningrum, L dan Siswantoro, D. (2014). Analysis the Effect of macroeconomic indicators and specific-firm characteristic as determinant profitability of Islamic banks in Asia. Journal Islamic Economic and Busines, 2(2), 85-97.Zulifiah, Fitri dan Joni Susilowibowo. (2014). Pengaruh inflasi, BI Rate, CAR, NPF, BOPO terhadap profitabilitas bank syariah 2008-2012.Jurnal Ilmiah Mahasiswa UNESA.